PENGARUH ISOTERM SORPSI AIR TERHADAP STABILITAS BERAS UBI [Effect of Moisture Sorption Isotherm to Stability of “Sweet Potato Rice”] - Sri Widowati; Heti Herawati; Rizal Syarief; Nugraha Edhi Suyatma; Hendra Adi Prasetia (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2010)
“Sweet Potato Rice” stability as a dry food product was determined by water activity (aw) and equilibrium moisture content (Me). This relationship is known as moisture sorption isotherm. This research were aimed 1) to study moisture sorption isotherm of “Sweet Potato Rice” from sweet potato flour (Cangkuang variety) and native/heat moisture treatment (HMT) starch which was stored at the range of aw:0.06 - 0.96 and 28oC; 2) to determine an appropriate model for describing product moisture sorption isotherm and 3) to predict “Sweet Potato Rice” shelf of life. Experimental design used was a random complete design with two factor, namely: 1) sweet potato starch: native and HMT, and 2) packaging material: polyethylene (PE) and polypropylene (PP).The result showed that the moisture sorption isotherm profiles were sigmoid. Smith equation was the best model which described moisture sorption isotherm with R2= 0,991-0,993 for adsorption and R2= 0,964-0,971 for desorption. Shelf life test showed that “Sweet Potato Rice” from Cangkuang flour and modified starch had longer shelf life (5.67 months when packed in PP bag and 2.3 months when packed in PE bag); while shelf life artificial sweet potato made from Cangkuang flour and native starch was 4.24 months when packed in PP bag and 1.72 months when packed in PE bag.